Clinical evaluation and in-vivo analysis of the performance of a fractional infrared 1550 nm laser system for skin rejuvenation. (18th August 2018) - Tidwell, W. James; Green, Courtney; Jensen, Daniel; Ross, E. Victor
ABSTRACT: Background : This study was done to demonstrate the safety and efficacy of a novel fractional 1550 nm laser device with a rolling mechanism (FRAX1550 Ellipse Medical, Horsholm, Denmark). Objectives : To evaluated the effectiveness of the 1550 nm device for improvement in wrinkles, pigmentation, and texture on a six point (−1 to 4) global improvement scale. Methods : Five female subjects between the ages of 44 and 71 years, with visible wrinkles and/or dyspigmentation were enrolled in the study. Two full face treatments were performed four weeks apart Follow-up visits at 1 and 3 months posttreatment were scheduled for photographic assessments. Assessment of improvement were performed by the investigators and two blinded evaluators through use of a six-point scale. Results : All subjects demonstrated improvement in all monitored parameters. The mean improvement scores were: wrinkles 1.6, skin texture 1.8, and pigmentation 1.7. All score improvements were statistically significant. Biopsy was performed on one patient immediately post-treatment and showed 800 μ penetration depth at a treatment level of 88 mJ and 400 μ at 44 mJ. Conclusions : The new rolling fractional 1550 nm laser device from this study offers improvement of aging facial skin with short downtime and minimal side effects.